New family of boost switched-capacitor seven-level inverters (BSC7LI) - Lee, Sze Sing; Bak, Yeongsu; Kim, Seok Min; Joseph, Anto; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2019)
This paper proposes a new family of multilevel inverter topology that is able to generate seven voltage levels by utilizing one or two floating capacitors and 10 power switches. This novel boost switched-capacitor seven-level inverter possesses voltage boosting capability with an achievable maximum voltage level 1.5 times the input direct current (dc) voltage. The generation of higher output voltage does not incur high-voltage stress on any power switch in this topology, as the peak inverse voltages of all power switches do not exceed the input source voltage. In addition, capacitor voltage balancing is not essential since the floating capacitors are effectively balanced during the charging and discharging processes. Furthermore, the proposed topology eliminates the need for multiple isolated dc sources, and a single dc source is sufficient in both its single-phase and three-phase topologies. The operating principle and steady-state analysis of the proposed topology are elaborated. Experimental results from a single-phase prototype are then presented to verify the validity of the proposed topology.
Keywords: Boost inverters; Capacitor voltage balancing; Direct current voltage; Higher output voltages; Inverter topologies; Multi Level Inverter (MLI); Multilevel inverter topology; Switched capacitor; Boost inverter; inverter topology; multilevel inverter (MLI); switched-capacitor